รูปแบบสถาปัตยกรรมไทยสมัยใหม่ : องค์ประกอบและส่วนประณีตสถาปัตยกรรม - จิรวัฒน์ เหลืองอร่าม (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The development of modern Thai architecture through the application of historical elements and ornaments reflects that a Thai style has obtained a rewarding result. This can be seen from the awards granted by the Association of Siamese Architects under Royal Patronage in cooperation with the Prince Wothayakorn Worawan Foundation where the prestigious awards were given to architectural works with modern Thai style designs that can express the basic characteristics of Thai architecture. However, there has been no distinctive trend on the development of modern Thai architecture yet. This is partly due to the different levels of perception and acceptance when applying Thai architectural elements and ornaments. This research was carried out by means of surveying modern Thai architectural patterns with respect to elements and ornaments together with the study of the original nature of the elements and ornaments in the past. It set up a guidance for the usage of Thai characteristics as well as for making simulated models to be applied in comparative investigation. In this regard, questionnaires were given to two groups of respondents, each group comprising 150 [persons] of architects and general people respectively. The objectives of this research were aimed to study Thai characteristics and the related suitability value arising from using Thai architectural [such as Kalae (the final on the eaves), eaves (wind breakers), gable apex, purlin head, angle braces and fenestration]: to compare modern Thai architecture created by architects with the modified models; to carry out a comparative study in the perception of style and the acceptance levels between those of architects and general people. According to this research, it was found that modern Thai architectural elements and ornaments with distinctive Thai style features such as Kalae, gable apex (Southern style), angle braces (Northern style), gable feature and indented corners of posts were suitable because the designs of such elements and ornaments were in accordance with those in the past. Therefore, the trend for developing modern Thai architecture should continue by means of using such features. This implied that such design should be performed in line with modern technology. Moreover, this research also showed that there were different views concerning the perception of modern Thai architecture and the trends of development as well. This was due to the result of learning processes and experiences in architectural education and profession. Architects should take the difference of views into consideration when designing architectural works to enable the general people to perceive and accept the characteristics of Thai style arising from using these modern Thai architectural elements and ornaments.